A Book Review: AI in Education Guidance for Policy Makers - Angga Widitama; Dahlia Linuwih; Elisha Giovanni Dyanu Permana (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
This book delves into AI's potential to revolutionize teaching, learning, and assessment while addressing ethical concerns and policy implications. The review commends the book's emphasis on equity, inclusion, and ethical considerations in AI adoption. It highlights the importance of interdisciplinary collaboration and robust governance frameworks to ensure AI's responsible and equitable implementation. The review also underscores the book's practical recommendations for leveraging AI to enhance educational management, empower educators, and foster lifelong learning. Overall, this review provides valuable insights into the transformative potential of AI in education and emphasizes the need for thoughtful and ethical approaches to maximize its benefits for all learners.